Polyclonal Regulatory T Cell Therapy for Control of Inflammation in Kidney Transplants. Issue 11 (14th August 2017) - Chandran, S.; Tang, Q.; Sarwal, M.; Laszik, Z. G.; Putnam, A. L.; Lee, K.; Leung, J.; Nguyen, V.; Sigdel, T.; Tavares, E. C.; Yang, J. Y. C.; Hellerstein, M.; et al.
Abstract : Early subclinical inflammation in kidney transplants is associated with later graft fibrosis and dysfunction. Regulatory T cells (Tregs) can reverse established inflammation in animal models. We conducted a pilot safety and feasibility trial of autologous Treg cell therapy in three kidney transplant recipients with subclinical inflammation noted on 6‐month surveillance biopsies. Tregs were purified from peripheral blood and polyclonally expanded ex vivo using medium containing deuterated glucose to label the cells. All patients received a single infusion of ~320 × 10 6 (319, 321, and 363.8 × 10 6 ) expanded Tregs. Persistence of the infused Tregs was tracked. Graft inflammation was monitored with follow‐up biopsies and urinary biomarkers. Nearly 1 × 10 9 (0.932, 0.956, 1.565 × 10 9 ) Tregs were successfully manufactured for each patient. There were no infusion reactions or serious therapy‐related adverse events. The infused cells demonstrated patterns of persistence and stability similar to those observed in non‐immunosuppressed subjects receiving the same dose of Tregs. Isolation and expansion of Tregs is feasible in kidney transplant patients on immunosuppression. Infusion of these cells was safe and well tolerated. Future trials will test the efficacy of polyclonal and donor alloantigen‐reactive Tregs for the treatment of inflammation in kidney transplants. Abstract : The first interventional trial utilizing ex vivo expanded autologous regulatory T cells to control graft inflammation in kidney transplantation demonstrates the therapy's safety and feasibility.